(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Every human research creates generalizable information which is an integral part of health improvement & understanding of disease. It also causes some risk or inconvenience to research participants. Codes of conduct for physicians have existed since ancient period. Declaration of Helsinki ICMR, Human subjects’ protection; Animal care guidelines etc provide a policy for conduct of research involving research participants in India. The Why & the How in research are vital questions. The ‘Why’ is very clear to define as improvement of public health. What matters more is the ‘How’: while performing it is necessary to adhere to research ethics for promotion of knowledge, truth and avoidance of errors. Research being team work, involves principles of team work such as trust, mutual respect, even handedness, and accountability. Upholding confidentiality, data sharing policies, guidelines of authorship, peer review policies, copyright and patenting policy promotes security of intellectual property and gives confidence for collaborations. Ethical research outlines standard guidelines for institutions and professionals for their behavior towards the specified goals and helps to develop the trust of community further promoting funding.